Cash holdings, corporate performance and viability of Greek SMEs: Implications for stakeholder relationship management. Issue 3 (22nd November 2019) - Dimitropoulos, Panagiotis; Koronios, Konstantinos; Thrassou, Alkis; Vrontis, Demetris
Abstract : Purpose: Several theories have been developed trying to explain the corporate decisions on cash holdings. Stakeholder theory is one of the arguments that urge firms with strong stakeholder relationships to hold more cash. The purpose of this paper is to shed further light on this issue by examining the impact of cash holdings on the financial performance and viability of Greek Small-Medium Enterprises before and after the Greek sovereign debt crisis. Design/methodology/approach: The authors collected a large sample from Small-Medium-sized Enterprises (SMEs) and a comparable sample from large firms operating in Greece during the period 2003–2016. Panel regression analysis was performed before and after the Greek debt crisis. Findings: Results indicated that cash holdings contribute positively to the profitability and viability of firms validating the precautionary theory of cash holdings in Greece. Before the crisis, SMEs and large firms both benefited significantly by cash holdings but after the crisis that positive impact of cash is more evident and significant for SMEs. Practical implications: These findings corroborate the hypotheses that during a period of limited lending (and severe financial turmoil); cash holdings (and effective cash management) could be a vital tool for sustaining SMEs' viability and financial performance. This study offers useful managerial implications and contributes to the ongoing debate about the impact of cash holdings on corporate performance. Originality/value: This is the first study in the Greek business setting trying to examine the impact of cash holdings on financial performance within stakeholder-oriented firms during a period of financial turmoil.